Pengembangan Pengelolaan Bank Sampah Demi Melindungi Lingkungan dan Meningkatkan Taraf Ekonomi Masyarakat di Kelurahan Sendangguwo, Kecamatan Tembalang, Kota Semarang - KMT Lasmiatun; Hardiwinoto Hardiwinoto; Ari Dwi Astono; Siti Hidayah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
DEVELOPMENT OF WASTE BANK MANAGEMENT TO PROTECT THE ENVIRONMENT AND IMPROVE THE ECONOMIC LEVEL OF THE COMMUNITY IN SENDANGGUWO VILLAGE, TEMBALANG DISTRICT, SEMARANG CITY. Suboptimal waste management is an environmental problem that has widespread impacts on community health, hygiene, and quality of life. The waste bank program presents an innovative solution for community-based waste management. This study aims to develop a waste bank management system in Sendangguwo Village, Tembalang District, Semarang City, to protect the environment while improving the economic well-being of residents. The research method used was a qualitative descriptive approach through observation, interviews, and documentation with managers and the surrounding community. The results indicate that waste bank development can reduce household waste volume by up to 40%, foster environmental awareness, and provide additional income for the community through the sale of sorted waste. Furthermore, recycling education and training activities also strengthen community empowerment. Thus, waste bank management has proven effective as an instrument for economic empowerment and environmental preservation at the local level.